Kebutuhan Ruang Parkir Pada Taman Tepian Pesut Mahakam, Kota Samarinda - Muhammad Zen Nabil Athallah; Rizky Arif Nugroho; Arief Hidayat; Maryo Inri Pratama (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2023)
Parking is one of the transportation infrastructure that must be managed properly to meet the needs of proper and adequate parking spaces. One of the transportation infrastructures is providing parking, both on-street parking and off-street parking. The Mahakam Tepian Pesut Park area is one of the most popular tourist areas visited by tourists and residents of Samarinda City. Along with the increase in the population of Samarinda City and the number of tourists visiting the Mahakam Pesut Edge Park Area, the impact on the reduction of parking lots. The purpose of this study was to analyze the need for parking space at the Mahakam Pesut Edge Park on Jalan Gadjah Mada. The research method used is descriptive quantitative method. The results show that the area of the research area used for parking is 830 m² and the need for parking is greater than the availability of parking. It is obtained that the existing conditions of parking for cars and motorbikes experience a shortage every year in the next 5 years and the addition of Parking Space Requirements (KRP) every year which does not include the addition of new parking lots. Keywords : Parking, Mahakam Pesut Edge Park, Parking Space Requirement